Prediction of Survival in Diffuse Large B Cell Lymphoma According to Immunohistochemistry - Cavolli, Viola; Georgievski, Borce (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: The introduction of chemoimmunotherapy in the treatment of diffuse large B cell lymphoma (DLBCL) dramatically improved the outcomes compared to chemotherapy alone. However, a significant part of the patients become refractory and eventually relapse. AIM: The purpose of this study is to analyze the survival differences between different groups of DLBCL according to Han’s algorithm. MATERIALS AND METHODS: We will study the medical records of 244 patients treated with RCHOP as first-line therapy who are diagnosed with de novo DLBCL in a cohort of 10 years in the University Clinical Center of Kosovo. According to immunohistochemical markers, the patients will be classified into two major groups, germinal center B cell-like (GCB) and non-germinal center B cell-like (non-GCB) subtypes, and five subgroups (Group 1, Group 2, Group 3 or double positive, Group 4, and Group 5 or triple negative [TN]). RESULTS: The patients in the GCB group have better progression-free survival (PFS) and overall survival (OS) than the non-GCB group. Despite this, double positive (DP) (CD10+MUM1+) and TN (CD10−Bcl6−MUM−) subgroups showed different PFS and OS to the same cell-of-origin group. The DP group showed similar OS and PFS with the non-GCB group, whereas the TN group showed similar OS and PFS with the GCB group. CONCLUSION: These factors will provide valuable knowledge for predicting the prognosis and redirecting the choice of treatment for different groups of DLBCL.